Historical and Geographical Reconstruction of the Figure of Dhul-Qarnayn in Surah Al-Kahf - Qoriatul Fitriyah; Muhammad Prihadi Eko Wahyudi (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
The identity of Dhul-Qarnayn in Surah Al-Kahf has been a perennial debate between Alexander the Great and Cyrus the Great. This study aims to reconstruct Dhul-Qarnayn's identity historically and validate his travel route using a topographical approach. This study uses critical historical methods and a comparative study of interpretations (classical and modern) combined with geographical data. The analysis shows that the characteristics of Cyrus the Great are more in line with the Qur'anic description of a just monotheist leader than Alexander, who worshipped many gods. The topographical approach identifies the "black muddy sea" and the "gap between two mountains" with geographical locations in the Caucasus region and the western border of Persian rule. This study emphasizes the importance of combining archaeological and geographical data in understanding the historical narrative of the Qur'an.